Endovascular Thrombectomy for Pediatric Acute Ischemic Stroke: A Multi-Institutional Experience of Technical and Clinical Outcomes. (18th December 2021) - Ravindra, Vijay M; Alexander, Matthew; Taussky, Philipp; Bollo, Robert J; Hassan, Ameer E; Scoville, Jonathan P; Griauzde, Julius; Awad, Al-Wala; Jumaa, Mouhammad; Zaidi, Syed; Lee, Jonathan J; Hafeez, Muhammad Ubaid; et al.
Graphical Abstract: